Optimizing Accounting for Amplang MSMEs in Ketapang through the Implementation of MSME Financial Accounting Standards using Google Spreadsheet - Lestary, Dini (Jurusan Akuntansi Politeknik Negeri Pontianak, 2024)
This article explores the optimization of accounting practices for Amplang Micro, Small, and Medium Enterprises (MSMEs) in Ketapang through the implementation of MSME Financial Accounting Standards (SAK EMKM). Leveraging the capabilities of Google Spreadsheet as a versatile application, this study focuses on streamlining financial reporting processes for MSMEs. The application of Google Spreadsheet allows for the automated input of journal transactions and initial balances, ensuring the validity of financial information. The results demonstrate that the utilization of spreadsheet applications enhances the practicality and ease of financial report preparation, particularly tailored for small and medium-sized enterprises like Amplang MSMEs. This research contributes valuable insights into the efficient integration of technology in accounting practices, fostering financial management improvements for businesses at the micro, small, and medium scales.